(untitled) (Latakia University Journal -Basic Sciences Series, 2016)
Proven chemical analyzes conducted in the summer of 2014 to thirty wells in the village AL-Shamia- Latakia region, that water wells west of the adjacent village to the seaside up to 300 m distance to the east where the salinity increases while decreasing the East Village to become water sweet near way of Lattakia-Kassab, at a distance of 1500 m fromn the sea beach. أثبتت التحاليل الكيميائية التي أجريت في صيف 2014 لثلاثين بئراً في قرية الشامية-منطقة اللاذقية أن مياه الآبار غرب القرية المتاخمة لشاطئ البحر حتى مسافة 300م شرقاً تزداد فيها الملوحة في حين تتناقص شرق القرية حتى تصبح مياهاً حلوة عند طريق اللاذقية كسب على مسافة 1500م عن شاطئ البحر.